Contemporary Arab contribution to world culture : an Arab-Western dialogue - Youssef, Magdi (Cambridge Scholars Publishing, 2018)
This book comprises a selection of papers delivered at a research meeting of the International Association of Intercultural Studies (IAIS) which took place on the premises of UNESCO in Paris in March, 2009. As suggested by its title, it addresses prejudices prevailing not only in Western societies, but also in marginalized ones, especially among their Western-oriented intelligentsia. It is often claimed that there exists no 'serious' contribution to world culture that is not based on the Western models that prevail worldwide, especially in the aftermath of globalization. This book challenges t.